The successful salvage of a thrombosed pancreatic graft at the early postoperative period of a simultaneous pancreas and kidney transplantation. (2018) - Shahbazov, Rauf; Azari, Feredun; Whan, Park Auh; Wei, Liu; Agarwal, Avinash; Brayman, Kenneth L.
Highlights: Transplanted pancreas venous thrombosis is a complex to diagnose. Urgent and prompt treatment is necessary. Endovascular pharmacomechanical thrombectomy sometimes possible. Early intervention can salvage graft organs in those receiving simultaneous pancreas and kidney transplantation. Abstract: Introduction: Simultaneous kidney and pancreas transplant is the preferred treatment option for end-stage renal disease due to type 1 diabetic nephropathy. Vascular complications are detrimental to graft survival and can lead to graft loss in the early postoperative phase of transplantation. Generally, duplex Doppler ultrasound is used for vascular patency monitoring and pancreatectomy followed by re-transplantation is required in the majority of cases. Recently, pancreatic graft salvage with non-operative management, including medical anticoagulation and endovascular thrombectomy, in the early postoperative period has been described with success. Presentation of case: We report a case of early detection of pancreas venous graft thrombosis via clinical suspicion and radiological methods, and early intervention with endovascular thrombolysis. As a result, the pancreatic graft was successfully salvaged. Discussion: A limited number of studies had showed successful graft salvage in only 30–45% of thrombosed pancreatic graft with surgical thrombectomy. Our patient also had bleeding from the vascular access site and ultimately required blood transfusion, however she recovered well after procedure. Conclusion: Given the complexity and significance of PVGT, urgent and prompt treatment is necessary. Interpreting outcomes from our case and other small studies, it appears that endovascular pharmacomechanical thrombectomy can be a vital tool to salvage graft organs in those receiving SPK.